Social fear memory requires two stages of protein synthesis in mice - Kornhuber, Johannes; Zoicas, Iulia (International Journal of Molecular Sciences, 2020)
It is well known that long-term consolidation of newly acquired information, including information related to social fear, require de novo protein synthesis. However, the temporal dynamics of protein synthesis during the consolidation of social fear memories is unclear. To address this question, mice received a single systemic injection with the protein synthesis inhibitor, anisomycin, at different time-points before or after social fear conditioning (SFC), and memory was assessed 24 h later. We showed that anisomycin impaired the consolidation of social fear memories in a time-point-dependent manner. Mice that received anisomycin 20 min before, immediately after, 6 h, or 8 h after SFC showed reduced expression of social fear, indicating impaired social fear memory, whereas anisomycin caused no effects when administered 4 h after SFC. These results suggest that consolidation of social fear memories requires two stages of protein synthesis: (1) an initial stage starting during or immediately after SFC, and (2) a second stage starting around 6 h after SFC and lasting for at least 5 h.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Anisomycin; Fear acquisition; Fear extinction; Fear learning; Fear memory; Memory consolidation; Protein synthesis; Social anxiety; Social fear; Social investigation